Case study : energy dissipater constructed in Kuantan - Nurbaitee, Mohamad Fauzi (2012)
In the construction of the man-made or natural channel, there are various problems that should be taking into consideration especially in the design of the hydraulic open channel. The presence of high flow velocity in open channel can destroy the function of the structure due to erosion and scouring along the channel bed. As a result, maintenance work will be costly. However, this problem can be overcome by reducing the flow velocities in the channel. In order to achieve this aim, an energy dissipater structure is proposed to be constructed in the channel. The objective of this study is to define the capability of discharge channel in the effect of various types of discharge channels, characteristic of flow and flow condition in stepped channel. This study is conducted in Kuantan area. There are five different types of discharge channel used in this study, that is channel without stepped, trapezoidal stepped channel, parabolic stepped channel, rectangular stepped channel and rectangular stepped channel with rock surface. From the graph plotted, a relationship between energy dissipation and different types of channel were gained. The results indicate that rectangular stepped channel with rock surface dissipates more energy compared to other types of discharge channels. Results also show that as the velocity of water increased, the energy dissipation is decreased. Generally, this study has proven that the stepped structure is effective in dissipate energy compared to channel without stepped in the hill area.